EFEKTIVITAS PENERAPAN RESTORATIVE JUSTICE DALAM PENANGANAN KASUS KECELAKAAN LALU LINTAS DI KEPOLISIAN RESOR KOTA SURAKARTA - Putri, Chalisna Paristiana; Pratiwi, Dian Esti (Legal Standing : Jurnal Ilmu Hukum, 2023)
Settlement of traffic accident cases through restorative justice at the Surakarta’s Police Resort Department as an alternative to the criminal justice system because it is considered more effective, efficient and does not take as long as the process in court. In fact, the application of restorative justice does not yet have specific laws and regulations and the public does not clearly understand the settlement of cases by implementing restorative justice. The purpose of this study is to analyze the effectiveness of the implementation and obstacles of restorative justice in handling traffic accident cases at the Surakarta’s Police Resort Department. This type of research is empirical research with data collection techniques through interviews. The research data analysis technique used the deduction method. The results of this study indicate that the Surakarta’s Police Resort Department Police in implementing restorative justice has done well because the majority of traffic accident cases are resolved using the restorative justice system. However, there are two obstacles in its implementation, namely from the factor of legal substance and the factor of society, especially cybercitizen.